On the Reduction of Ammonia from the Waste of Alpine Houses - Sameer Al-Asheh; Franz Bischof (Adsorption Science & Technology)
An evaluation of the effectiveness of the cation-exchange resin Amberlite IR-120 (AMIR 120) for removing ammonia from aqueous solutions and waste was made. Two types of waste were obtained from houses located in the Alps and used in this work. The results of the study showed that AMIR 120 may be considered as a suitable material for the removal of ammonia from aqueous and waste systems. The amount of ammonia removed increases with increasing AMIR 120 concentration. Sorption of ammonia decreases as the pH of the aqueous solutions increases. The Langmuir model represents the experimental data reasonably well.